2015
DOI: 10.1007/s13277-015-4029-3
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces apoptosis in p53-null Hep3B cells through a TAp73/DNp73-dependent pathway

Abstract: Curcumin has anticancer functions in various tumors. It has been shown to induce apoptosis through p53-dependent pathways. p73 gene is a member of the p53 family which encodes both a tumor suppressor (transactivation-competent p73 (TAp73)) and a putative oncogene (dominant-negative p73 (DNp73)); the former shares similarity with the tumor suppressor p53, and the latter behaves as dominant-negative proteins that interfere with the activity of TAp73. To understand the p73-dependent mechanisms that are engaged du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Our data showed that TAp73 and Elk-1 were highly upregulated after rubone monotherapy or PTX and rubone combination therapy (Figure 3F and G). This discrepancy may be explained by the extremely low expression of TAp73 (37) and Elk-1 (38) in Hep3B cells compared to PC3-TXR cells, which means that all known miR-34a regulation pathways are blocked in Hep3B cells. Thus, we conclude that rubone might work as a miR-34a modulator for prostate cancer in a p53 independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that TAp73 and Elk-1 were highly upregulated after rubone monotherapy or PTX and rubone combination therapy (Figure 3F and G). This discrepancy may be explained by the extremely low expression of TAp73 (37) and Elk-1 (38) in Hep3B cells compared to PC3-TXR cells, which means that all known miR-34a regulation pathways are blocked in Hep3B cells. Thus, we conclude that rubone might work as a miR-34a modulator for prostate cancer in a p53 independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 may induce apoptosis extrinsic or intrinsic pathway triggered via cellular stresses from nutrient deprivation and hypoxia, DNA damage, proliferation and cell survival [293,294]. Curcumin, a yellow pigment of diarylheptanoid isolated from rhizome of Curcuma longa has been extensively studied on its apoptosis inducing capabilities on various cancer cell lines involving p53 modulation [295,296,297]. p53 upon activation, triggered the mitochondria apoptotic pathway by acting as transcription factor that regulates the expression of pro-apoptotic Bcl-2 family member mainly Bax, BH3,phorbol-12-myristate-13-acetate-induced protein 1 (NOXA), and PUMA, and down-regulates the anti-apoptotic Bcl-2, Bcl-xL, and inhibitors of apoptosis proteins (IAPs), which includes Survivin [298].…”
Section: Molecules Target and Signaling Pathway Of Apoptosis Inducmentioning
confidence: 99%
“…So, the repression of p21 after KCTD11 knock-down in Huh7 could be a result of up-regulated MST1/GSK3β. To further confirm this mechanism, we estimated the changes of Hippo pathway and p21 signaling in the p53-deficient Hep3B cells [28]. Hep3B was treated by siRNA of KCTD11.…”
Section: Resultsmentioning
confidence: 99%